2018
DOI: 10.1186/s12944-018-0800-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various lipid parameters in association of target organ damage: a cohort study

Abstract: BackgroundRecommendations of non-HDL amplification varied from different guidelines. We aim to test the relationships between various lipid parameters and target organ damage (TOD) including aortic stiffness, peripheral arterial disease and chronic kidney disease in a community-based elderly cohort.Methods1599 (aged 71.4 ± 6.1 years) participants were recruited. Eight lipid parameters, including total cholesterol (TC), triglycerides (TG), LDL-C, HDL-C, non-HDL-C, TC/HDL ratio, TG/HDL ratio and LDL/HDL ratio, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…5,6 Several other studies also showed that the F I G U R E 3 Hazard ratios for the association of a unit increase in LDL-C, TC to HDL-C ratio and triglyceridse variability with the composite outcome (CVD and mortality) from Cox regression models adjusted for baseline covariates. A separate model is fitted for each specified subgroup TC to HDL-C ratio was a stronger predictor of CVD risk, 29 and was included in the risk prediction model for CVD rather than individual TC and HDL-C. 13 However, previous studies have focused on a single effect but not the joint effect of TC and HDL-C variability on CVD risk 4,5,7,9 and therefore our findings help to extend the current evidence regarding the positive linear association between the TC to HDL-C ratio variability and CVD risk. It should also be noted that the results showed a decreased magnitude of effect of LDL-C variability on CVD risk after LDL-C variability of 0.5 mmol/L ( Figure S4A), although no literature to date has explored this observation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Several other studies also showed that the F I G U R E 3 Hazard ratios for the association of a unit increase in LDL-C, TC to HDL-C ratio and triglyceridse variability with the composite outcome (CVD and mortality) from Cox regression models adjusted for baseline covariates. A separate model is fitted for each specified subgroup TC to HDL-C ratio was a stronger predictor of CVD risk, 29 and was included in the risk prediction model for CVD rather than individual TC and HDL-C. 13 However, previous studies have focused on a single effect but not the joint effect of TC and HDL-C variability on CVD risk 4,5,7,9 and therefore our findings help to extend the current evidence regarding the positive linear association between the TC to HDL-C ratio variability and CVD risk. It should also be noted that the results showed a decreased magnitude of effect of LDL-C variability on CVD risk after LDL-C variability of 0.5 mmol/L ( Figure S4A), although no literature to date has explored this observation.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study including 107 patients with type 2 diabetes in Taiwan, Lee et al found that TC/HDL-C showed an inverse trend to change in ABI (β = −0.212, 95% CI: −0.043-−0.001) [11]. Another post hoc data analysis from randomized controlled trial, conducted in 1599 community-based elderly cohort, reported that TC/HDL-C ratio (OR:1.31; 95% CI: 1.14-1.49), non-HDL-C (OR: 1.15; 95% CI: 1.01-1.31) and LDL-C/HDL-C ratio (OR:1.25; 95% CI:1.10-1.43) had a signi cant correlation with PAD [12]. Moreover, another population-based study from the elderly in rural China also found a signi cant correlation between LDL-C/HDL-C and PAD (highest compared with lowest tertile; OR: 2.56; 95% CI, 1.37 to 4.81) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increasing studies have indicated development and progression of atherosclerosis on the condition of abnormal nontraditional lipid pro le. It has recently been proposed that triglyceride (TG)/HDL-C ratio is a favorable predictor of cardiovascular disorders [6][7][8][9], and some studies have suggested that the total cholesterol (TC)/HDL-C ratio is also closely related to cardiovascular disease (CVD) [10][11][12]. Indeed growing evidence has established the associations between LDL-C/HDL-C ratio and carotid plaque score [13], carotid intima media thickness [14], and PAD [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…По результатам когортного исследования C.Chi с соавт. (2018) привлекают внимание к тесным взаимосвязям с повреждением органов-мишеней (включая жесткость аорты -aortic stiffness, заболевания периферических артерий и ХБП и считая их определяющим фактором КМР) именно комбинированных липидных индексов в отличии от отдельных липидных показателей [48]. Результаты перекрестного исследования (n=17596) подтверждают высокую корреляцию TG/HDL-C с факторами КМР и субклиническим повреждением органов-мишеней.…”
unclassified